In search of lost engagement: gamification in synchronous remote teaching in business administration and its effects on continuance intention and perceived learning effectiveness - Pardim, Vanessa Itacaramby (2024)
This thesis, grounded in the theoretical lenses of Self-Determination Theory and the Stimulus-Organism-Response model, analyzed the effects of using gamification, supported by Digital Information and Communication Technologies (DICTs) and adapted to different player types, in teaching Administration, considering the possibility of continuing synchronous remote teaching as part of the process of hybridizing face-to-face teaching. The research investigated factors influencing students intention to continue using this format and, subsequently, the impact of gamification on engagement and perceived learning effectiveness. Structured in an article-based format, the study employed a combined methodological approach, integrating methods such as Structural Equation Modeling, Artificial Neural Networks, Necessary Condition Analysis, and fuzzy-set Qualitative Comparative Analysis. The first two articles analyzed the factors influencing students intention to continue using synchronous remote education. Ease of use and perceived enjoyment proved crucial for this format\'s acceptance and long-term adoption. Since perceived enjoyment was necessary, significant, and the strongest factor in the intention to continue using synchronous remote education, the next step involved developing the third article, which conducted a bibliometric study and a systematic literature review. The objective was to provide a comprehensive map of scientific knowledge on the adoption of gamification in the teaching-learning process in Administration courses, highlighting the key elements and DICTs used to enable such strategies. The fourth article explored the implementation of the 1.0 model of gamification that occurred during the pandemic period. This model emphasized the use of immersion, competition, and network exposure as essential factors for engaging students with gamified activities in a synchronous remote context. Anxiety and experience emerged as two important moderators, as students with high levels of anxiety might feel less engaged in gamified activities involving intense competition or online exposure. Conversely, more experienced students tended to engage less, underscoring the importance of using varied and challenging resources. The fifth study focused on the 2.0 model of gamification, offering a fully gamified course in the context of post-pandemic synchronous remote education. In this model, all course components were structured based on gamification elements designed to accommodate all player profiles (Socializers, Achievers, Explorers, Philanthropists, Free Spirits, and Disruptors). In this study, the theoretical model advanced compared to the one applied in the 1.0 model by introducing constructs such as perceived enjoyment of gamification as an independent variable and perceived learning effectiveness as a dependent variable. At the same time, engagement was treated as an independent variable. This change allowed for an analysis that extended beyond engagement, which, although important, does not necessarily reflect how effectively students perceive their learning. In conclusion, the study suggests that gamification, when adapted to different player profiles and supported by DICTs, can significantly transform the learning experience in synchronous remote education.